2019
DOI: 10.1096/fj.201900812r
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exercise prevents hepatic steatosis: a novel role of FABP1 in regulation of autophagy‐lysosomal machinery

Abstract: Nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent diseases worldwide. Exercise is a first‐line therapy and an important preventive measure for patients with NAFLD, but the underlying mechanisms are not clear. C57BL/6 mice were fed a high‐fat diet (HFD) and subjected to 12 wk swimming exercise. Exercise protected against hepatic lipid accumulation and alleviated hepatocyte damage in HFD mice. Tandem mass tag—based quantitative proteomic analyses and ingenuity pathway analysis revealed that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 59 publications
(69 reference statements)
2
29
0
1
Order By: Relevance
“…S3a,b). Consistent with this hypothesis, a previous study has shown that the overexpression of FABP1 in the mouse liver promotes non-alcoholic fatty liver disease [52].…”
Section: Discussionsupporting
confidence: 65%
“…S3a,b). Consistent with this hypothesis, a previous study has shown that the overexpression of FABP1 in the mouse liver promotes non-alcoholic fatty liver disease [52].…”
Section: Discussionsupporting
confidence: 65%
“…Defective lysosomal biogenesis and clearance impair autophagic flux, leading to intracellular lipid accumulation during the development of NAFLD (Chao et al, 2018b). Previous studies found that HFD disrupted lysosomal biogenesis in hepatocytes, which was associated with lipid degradation (Pi et al, 2019). We employed lysosomal inhibitor CQ to further investigate autophagy-lysosomal pathway involvement and found that liraglutide stimulated autophagic flux, as demonstrated by a reduction in autophagosome accumulation indicated by mRFP-GFP-LC3.…”
Section: Discussionmentioning
confidence: 94%
“…Lysosomes are organelles involved in the process of intracellular substrate degradation through autophagosomelysosome fusion and play a critical role in regulating autophagic flux and lipid droplet clearance. Normally, lysosomal lipid degradation capacity depends on a sufficient number of lysosomes and the activation of acid hydrolase enzymes (Sinha et al, 2014;Pi et al, 2019). Transcription factor EB (TFEB), Abbreviations: GLP-1RA, glucagon-like peptide-1 receptor agonist; NAFLD, non-alcoholic fatty liver disease; GLP-1R, glucagon-like peptide-1 receptor; PA, palmitic acid; TFEB, transcription factor EB; siRNA, small interfering RNA; LC3-II, microtubule-associated protein 1B light chain-3-II; HFD, high-fat diet; IGPTT, intraperitoneal glucose tolerance test; ITT, insulin tolerance test; TG, serum triglycerides; TC, total cholesterol; LDL-C, low-density lipoprotein cholesterol; ALT, alanine transferase; AST, aspartic acid transaminase; FBS, fetal bovine serum; OA, oleic acid.…”
mentioning
confidence: 99%
“…Also quercetin, a flavonoid found in various fruits and vegetables, anthocyanins from sweet cherries, and trehalose, a naturally occurring disaccharide derived from cocoons, have been reported to activate hepatic autophagy and reduce hepatic lipid content ( 115 , 116 , 124 , 125 ). In mice, long-term exercise protects against high-fat diet-induced hepatic lipid accumulation at least partly by increasing the autophagic flux ( 117 ). Fasting, intermittent fasting, caloric restriction and caloric restriction mimetic drugs all induce autophagy in various tissues including the liver and could therefore also be used as a strategy to reduce hepatic steatosis ( 118 120 ).…”
Section: Pre-clinical Studies On the Role Of Lipophagy In Non-alcoholmentioning
confidence: 99%